Simultaneous gallbladder-preserving cholecystolithotomy and laparoscopic splenectomy as a surgical option for hereditary spherocytosis in a child: A case report - Yutaka Yamada; Akinori Sekioka; Akiyoshi Nomura; Kei Oyama; Toshiaki Takahashi; Masaya Yamoto; Koji Fukumoto; Naoto Urushihara (Elsevier, 2017)
For hereditary spherocytosis complicated by cholelithiasis, cholecystectomy is simultaneously performed with splenectomy. However, jaundice promptly disappears after removing the spleen, and the risk for recurrent cholelithiasis decreases in majority of cases; gallbladder-preserving cholecystolithotomy can be an option for such patients. We report a case of a 6-year-old boy with hereditary spherocytosis who was referred by a previous physician for the chief complaint of anemia (hemoglobin level, 7-8 g/dl). Abdominal ultrasound and CT revealed numerous small calculi in the spleen and gallbladder. The patient developed calculous cholecystitis twice. Hence, laparoscopic splenectomy and gallbladder-preserving cholecystolithotomy were simultaneously performed. The operating time was 2 h and 58 min, and the blood loss was 45 ml. No postoperative complication developed, and the patient was discharged 5 days after the operation. To date, i.e., a year after the operation, no recurrent cholelithiasis has been observed in the patient.